How important is the Morphology of the Semen Analysis? - Entela Shkembi; Evin Dani; Nicola Daniele; Francesco Zinno; Gallo Emiliano Omar (Annals of Cytology and Pathology - Peertechz Publications, 2016)
Introduction: Male infertility is evaluated throughout the quantitative and qualitative analysis of male's semen and the sperm contained therein. One of the most essential part of this process is the evaluation of the cytomorphology of man's semen. We could reach a correct measurement of the morphology using stained smears that allow the differentiation of other cells like white blood cells and immature sperm cells that could indicate an infection or inflammation. Case report: This article reports two case studies of patients with examination results as below: Conclusion: Disorders in the mechanism of oocyte activation could be one of the origins of unsuccessful Intra- cytoplasmic sperm injection (ICSI). Normally this process starts with the spermoocyte merging, inducted from a calcium influx into the oocyte. The level of calcium alteration trigger factor is generated from an acrosome's component called phospholipase C zeta (PLCz). If this is absent (as in men with globozoospermia), then assisted oocyte activation needs to achieved by alternative means, such as by using a calcium ionophore.